Characterization of Kaolin Deposits in Kutigi, Niger State, Northern Nigeria - Joseph, Samuel Ominu; Olalekan, David Adeniyi; Moses, Aderemi Olutoye; Isah, Abubakar Garba; Sallau, Alhassan Adeku (Walisongo Journal of Chemistry, 2023)
Kaolinite is among the most important mineral resource of kaolin clay sample with numerous industrial applications. Its effective characterization in terms of its chemical composition, structure and thermal properties is important for streamline it specific industrial application. In this study, the mineralogical, thermal properties, surface morphology, surface area, structural functional groups and chemical compositions were determined using the X-ray diffraction (XRD), thermogravimetry analyser, scanning electron microscope (SEM), nitrogen adsorption-desorption BET, Fourier transform infrared spectroscopy (FTIR) and X-ray fluorescence (XRF) method. The major phases in the kaolin clay samples was the kaolinite with quartz, orthoclase, and albite as minor phases. the kaolin sample loss in weight was due to dihydroxylation. The kaolin particles were made of agglomeration of its irregular sized particles. The BET surface area of kaolin sample was 181.549 m2/g, with particle size of 2.98 nm and pore volume of 0.161 cc/g. The FTIR spectra showed presence of peaks for Si-O at positions 2359.48,1217.35, 1032.21, and 753.55 cm-1, while the Al-O group appeared at 1365.84, 912.65 and 668.21 cm-1. Elemental composition content results from XRF showed that SiO2 was 34.25 wt %, Al2O3 was 28.16 wt % as the major content while the minor content such as Fe2O3, MgO, TiO2, CeO2, K2O and ZrO2 were 1.17, 1.63, 1.59, 0.95, 0.37, and 0.27 wt % respectively.